Mixité fonctionnelle et nouveaux lieux de vie et de travail : quel potentiel pour Bruxelles face à l’expansion du travail hybride ? - Constance Uyttebrouck (Netcom)
The renewed intertwining of living and working places is not a recent phenomenon. Enabled by the development of information and communication technologies and the advent of the knowledge economy, it has genuinely affected cities. For several years, cities have integrated mixed-use principles into their urban development strategies, and they have seen new kinds of living and working places emerge. The Covid-19 pandemic has accelerated these changes by allowing the expansion of “hybrid work”, hence raising multiple questions for urban planning. Using Brussels (Belgium) as a case study, this paper examines the potential of mixed-use and new living and working places to address the issues related to hybrid work expansion. More specifically, we reflect on the future development of Brussels, based on mixed-use projects developed in urban regeneration areas and current discourses on “post-Covid” planning. Overall, this paper aims to contribute to current debates on the evolution of urban development principles under major crises such as pandemics.